Prognostic factors of survival in patients with gastric cancer: a retrospective study in the Aktobe region for 2010-2024. (Bangladesh Journal of Medical Science, 2025)
Relevance Gastric cancer (GC) remains a leading cause of cancer mortality, with survival rates heavily dependent on early detection. Most cases are diagnosed at advanced stages, resulting in poor prognoses and low 5-year survival rates. Accurate survival estimates are essential for assessing treatment effectiveness and guiding healthcare strategies. However, data collection delays hinder timely analysis. Model-based period analysis addresses this issue, enabling real-time survival estimates and forecasting trends to improve patient outcomes and cancer management. Aims To evaluate the prognostic factors influencing survival in patients with gastric cancer, considering demographic, clinical, and histopathological characteristics in the Aktobe region from 2010 to 2024. Methods A retrospective study was conducted using data from 1859 GC patients registered in the Aktobe Cancer Registry. Survival analysis was performed using Kaplan-Meier estimation, log-rank tests, and Cox proportional hazards models. Factors such as age, sex, tumor stage, histological subtype, tumor location, and ethnicity were analyzed for their impact on survival. Results The overall five-year survival rate was 21.5%. Advanced tumor stage was the most significant prognostic factor, with stage IV patients having significantly worse survival than stage I (p = 0.0124). Ethnicity was associated with survival differences, with non-Kazakh patients showing a higher risk of mortality (p = 0.0334). However, age, sex, tumor location, and Lauren classification did not show a statistically significant impact on survival. Patients with localized GC had significantly better survival outcomes compared to those with advanced disease (p < 0.001). Conclusion Tumor stage and ethnicity were identified as key prognostic factors affecting GC survival, while other clinical variables had less predictive value. These findings highlight the need for improved early detection strategies and targeted interventions to enhance patient outcomes. Further research incorporating molecular profiling may improve individualized treatment approaches.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 538-553